The Geometries, Stabilities and Electronic Property of Cationic Vanadium Doped Germanium Cluster GenV+ (n=9-13) from Density Functional Theory - Huu Tho, Nguyen; Tu, Trang Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4, 2019)
Geometries associated relative stabilities, averaged binding energy, fragmentation energy, second-order energy difference and energy gaps of V-doped germanium cationic clusters Ge n V + (n = 9-13) have been investigated by using density functional theory with the BP86 exchange-correlation potential and effective core potential (ECP) LanL2DZ basis sets. Natural population analysis charge is also examined to understand the associated charge transfer in structures of clusters. When an electron is removed from neutral cluster GenV to form the cation cluster Ge n V + , geometric structure of the lowest energy isomers change. The endohedral cage structure of the cation clusters appears at n = 10 in the cluster Ge 10 V + . The lowest energy isomers of cation cluster are in triplet state or singlet state. The cluster Ge 10 V + is found to be the most stable in terms of stability parameters in the all system Ge n V + (n = 9 - 13). Keywords: BP86/LANL2DZ, binding energy, V-Ge clusters, structure of clusters. References [1] T. Fehlner, J. Halet, J. Saillard, Molecular Clusters: A Bridge to Solid-State Chemistry, Cambridge University Press, Cambridge, 2007. https://doi.org/10.1017/CBO9780511628887. [2] S. Djaadi, K. Eddine Aiadi, S. Mahtout, First principles study of structural, electronic and magnetic properties of SnGen(0, ±1) (n = 1–17) clusters, J. Semicond., 39(4) (2018) 42001. https://doi.10.1088/1674-4926/39/4/042001. [3] P.N. Samanta, K.K. Das, Electronic structure, bonding, and properties of SnmGen (m+n≤5) clusters: A DFT study, Comput. Theor. Chem., 980 (2012) 123-132. https://doi.org/10.1016/j. comptc.2011.11.038. [4] S. Mahtout, Y. Tariket, Electronic and magnetic properties of CrGen (15≤n≤29) clusters: A DFT study, Chem. Phys., 472 (2016) 270-277. https://doi.org/10.1016/j.chemphys.2016.03.011. [5] A.A. Shvartsburg, B. Liu, Z. Y. Lu, C. Z. Wang, M.F. Jarrold, K. M. Ho, Structures of Germanium Clusters: Where the Growth Patterns of Silicon and Germanium Clusters Diverge, Phys. Rev. Lett., 83(11) (1999) 2167-2170. https://doi.org/ 10.1103/PhysRevLett.83.2167. [6] S. Bals, S. Van Aert, C. P. Romero, et al., Atomic scale dynamics of ultrasmall germanium clusters, Nat. Commun., 3 (2012) 897. https://doi.org/10. 1038/ncomms1887. [7] J. De Haeck, T. B. Tai, S. Bhattacharyya, et al., Structures and ionization energies of small lithium doped germanium clusters, Phys. Chem. Chem. Phys., 15(14) (2013) 5151-5162. https:// doi.org/ 10.1039/C3CP44395G. [8] G.R. Burton, C. Xu, D.M. Neumark, Study of small semiconductor clusters using anion photoelectron spectroscopy: germanium clusters, Surf. Rev. Lett., 03(01) (1996) 383-388. https:// doi.org/10.1142/S0218625X96000693. [9] P.W. Deutsch, L.A. Curtiss, J.P. Blaudeau, Electron affinities of germanium anion clusters, Gen− (n=2–5), Chem. Phys. Lett., 344(1) (2001) 101-106. https://doi.org/10.1016/S0009-2614(01) 00734-5. [10] J. Wang, G. Wang, J. Zhao, Structure and electronic properties of Gen (n=2-5) clusters from density-functional theory, Phys. Rev. B., 64(20) (2001) 205411. https://doi.org/10.1103/PhysRevB. 64.205411. [11] W.J. Zhao, Y.X. Wang, Geometries, stabilities, and magnetic properties of MnGen (n=2–16) clusters: Density-functional theory investigations, J. Mol. Struct. THEOCHEM., 901(1) (2009)18-23. https://doi.org/10.1016/j.theochem.2008.12.039. [12] W.J. Zhao, Y.X. Wang, Geometries, stabilities, and electronic properties of FeGen (n=9–16) clusters: Density-functional theory investigations, Chem. Phys., 352(1) (2008) 291-296. https://doi. org/10.1016/j.chemphys.2008.07.006. [13] S. Shi, Y. Liu, C. Zhang, B. Deng, G. Jiang G, A computational investigation of aluminum-doped germanium clusters by density functional theory study, Comput. Theor. Chem., 1054 (2015) 8-15. https://doi.org/10.1016/j.comptc.2014.12.004. [14] X. Li, K. Su, X. Yang, L. Song, L. Yang, Size-selective effects in the geometry and electronic property of bimetallic Au–Ge nanoclusters, Comput. Theor. Chem., 1010 (2013) 32-37. https:// doi.org/10.1016/j.comptc.2013.01.012. [15] N. Kapila, V.K. Jindal, H. Sharma, Structural electronic and magnetic properties of Mn, Co, Ni in Gen for (n=1–13), Phys. B Condens. Matter., 406(24) (2011) 4612-4619. https://doi.org/10. 1016/j.physb.2011.09.038. [16] C. Tang, M. Liu, W. Zhu, K. Deng, Probing the geometric, optical, and magnetic properties of 3d transition-metal endohedral Ge12M (M=Sc–Ni) clusters, Comput. Theor. Chem., 969(1) (2011) 56-60.https://doi.org/10.1016/j.comptc.2011.05.012. [17] A.K. Singh, V. Kumar, Y. Kawazoe, Metal encapsulated nanotubes of germanium with metal dependent electronic properties, Eur. Phys. J. D-Atomic, Mol Opt Plasma Phys., 34(1-3) (2005) 295-298. https://doi.org/10.1140/epjd/e2005-00162-1. [18] X.J. Deng, X. Y. Kong, H. G. Xu, X. L. Xu, G. Feng, W. J. Zheng, Photoelectron Spectroscopy and Density Functional Calculations of VGen– (n = 3–12) Clusters, J. Phys. Chem. C, 119(20) (2015) 11048-11055. https://doi.org/10.1021/jp 511694c. [19] C. Siouani, S. Mahtout, S. Safer, F. Rabilloud, Structure, Stability, and Electronic and Magnetic Properties of VGen (n = 1–19) Clusters, J. Phys. Chem. A, 121(18) (2017) 3540-3554. https://doi. org/10.1021/acs.jpca.7b00881. [20] S.P. Shi, Y.L. Liu, B.L. Deng, C.Y. Zhang, G. Jiang, Density functional theory study of the geometrical and electronic structures of GenV(0,±1)(n=1–9) clusters, Int. J. Mod. Phys. B, 31(05) (2016) 1750022. https://doi.org/10.1142/ S0217979217500229. [21] N. Huu Tho, T.T. Tu, T.M. Nhan, P.H. Cam, P.T. Thi, The Geometries and Stabilities of Neutral and Anionic Vanadium-Doped Germanium Clusters VGen0/- (n = 9-13): A Density Functional Theory Investigation, VNU J. Sci. Nat. Sci. Technol. 35(1) (2019) 47-56. https://doi.org/10. 25073/2588-1140/vnunst.4827. [22] W.R. Wadt, P.J. Hay, Ab initio effective core potentials for molecular calculations. Potentials for main group elements Na to Bi, J. Chem. Phys., 82(1)(1985)284-298. https://doi.org/10.1063/1.448800 [23] P.J. Hay, W.R. Wadt, Ab initio effective core potentials for molecular calculations. Potentials for K to Au including the outermost core orbitals, J. Chem. Phys., 82(1) (1985) 299-310. https://doi. org/10.1063/1.448975. [24] P.J. Hay, W.R. Wadt, Ab initio effective core potentials for molecular calculations. Potentials for the transition metal atoms Sc to Hg, J. Chem. Phys., 82(1) (1985) 270-283. https://doi.org/10. 1063/1.448799. [25] G. Manca, S. Kahlal, J.Y. Saillard, R. Marchal, J. F. Halet, Small Ligated Organometallic Pdn Clusters (n=4−12): A DFT Investigation, J. Clust. Sci., 28(2) (2017) 853-868. https://doi.org/10. 1007/s10876-017-1168-2. [26] T.D. Hang, H.M. Hung, L.N. Thiem, H.M.T. Nguyen, Electronic structure and thermochemical properties of neutral and anionic rhodium clusters Rhn, n=2–13. Evolution of structures and stabilities of binary clusters RhmM (M=Fe, Co, Ni; m=1–6), Comput. Theor. Chem., 1068 (2015) 30-41. https://doi.org/10.1016/j.comptc.2015.06. 004. [27] M.J. Frisch H.B. Schlegel, G.E. Scuseria, M.A. Robb, J.R. Cheeseman, G. Scalmani, V. Barone, G.A. Petersson, H. Nakatsuji, X. Li, M. Caricato, A. Marenich, J. Bloino, B. G. Janesko, R. Gomperts, B. Mennucci, H. P. Hratchian, J. V. Ortiz, A. F. Izma GWT. Gaussian 09, Revision C.01. Gaussian, Inc, Wallingford CT. 2010. [28] A.E. Reed, L.A. Curtiss, F. Weinhold, Intermolecular interactions from a natural bond orbital, donor-acceptor viewpoint, Chem. Rev., 88(6) (1988) 899-926. https://doi.org/10.1021/ cr00088a005.